Association between AHR in EGCs and IBS-D patients: the indole pathway of tryptophan metabolism - Wang, Lianli; Zhang, Yue; Ran, Yan; Li, Laifu; Mei, Lin; Ye, Fangchen; Sun, Yating; Wang, Ting; Quan, Xiaojing; Shi, Haitao; Dai, Fei (Frontiers in Nutrition, 2025)
BackgroundThe pathophysiological mechanisms of irritable bowel syndrome (IBS) are intricate, and associated with tryptophan metabolites. This study was designed to investigate the relationship between indole metabolites in the feces and intestinal function in patients with IBS.MethodsIn this study, 42 patients with diarrhea-predominant IBS (IBS-D) and 36 healthy controls were recruited. The symptom severity was evaluated using IBS-quality of life (IBS-QOL) and IBS symptom severity system (IBS-SSS). The levels of indole metabolite in fecal samples were determined by means of mass spectrometry. Colon mucosal tissues were collected during colonoscopy procedures. Immunohistochemistry or immunofluorescence techniques were employed to analyze the expressions of the aryl hydrocarbon receptor (AHR), cytochrome P450 1A1 (CYP1A1), glial fibrillary acidic protein (GFAP), S100 calcium-binding protein B (S100B), zonula occludens-1 (Zo-1), occludin, substance P (SP), nerve growth factor (NGF), NOD-like receptor family pyrin domain containing 3 (NLRP3), and nuclear factor kappa B (NF-κB) in the mucosal tissues.ResultsCompared with healthy controls, the concentrations of the main indole metabolites (p = 0.020), and the expressions of CYP1A1 (p < 0.001), and Zo-1 (p = 0.017) were decreased in patients with IBS-D, but the expressions of S100B (p < 0.001), NF-κB (p = 0.006), and NRLP3 (p = 0.041) were increased. Immunofluorescence analysis demonstrated the co-expression of AHR with GFAP or S100B. Moreover, the ratio of S100B/AHR (p = 0.011) was higher in IBS-D patients than in health controls. This ratio was positively correlated with IBS-SSS score (r = 0.47, p = 0.006), as well as with the expression levels of NRLP3 (r = 0.505, p = 0.019), NF-κB (r = 0.548, p = 0.01), and SP (r = 0.832, p < 0.01).ConclusionPatients with IBS-D exhibited low-grade inflammation in the colon mucosal tissues, compromised intestinal barrier function, and abnormal visceral sensation. This may be attributed to the decreased levels of tryptophan indole metabolites, the heightened activity of enteric glial cells (EGCs), and the inhibition of AHR/CPY1A1 signaling pathway.